The osteocyte - Bonewald, Lynda F. (Henry Stewart Talks, 2015)
Osteocyte description & research history, Technology used for studying osteocytes, Osteocytic osteolysis, Osteocytes as mechanosensory cells, Osteocytes as secretory cells regulating skeletal remodeling, Osteocytes as endocrine cells that target kidney and muscle